The effect of internal communication on employee performance: a case of Colmar Tropicale, Bejaya Hills / Nur Aqilah Shahruddin and Siti Wardah Ramli - Shahruddin, Nur Aqilah; Ramli, Siti Wardah (2019)
The good working environment is one of the choices choose by the new employees when looking for the right place to apply the working place. It is very importance thing to have a good working environment. The workplace area could be so challenging and stressful environment if there is poor communication in the organization. In addition, the good communication within the organization could lead to employee performance. The employee performance is influenced by several variables which are commitment, competency and cooperation among the staffs at Colmar Tropicale Beijaya Hills. This study will be conducted at Colmar Tropicale Beijaya Hills, regarding the effect of internal communication on employee performance within the organization. Since, there are no strong evidence on what factors that influenced the employee performance so this study is aim to identify the effects of internal communication on employee performance and also wants to know if the communication in the organization is good or poor communication. Based on the outcomes gained from the respondents among the employees which give the results that the organizations have a strong internal communication and it does give effects on employee performance.